Avaliação da dor à inserção do sistema intrauterino liberador de Levonorgestrel entre nulíparas e multíparas - Isabella Andrade de Resende Chaves (2021)
Introduction: The levonorgestrel-releasing intrauterine system (LNG-IUS) is a safe and effective method of non-permanent contraception that can be used by women, including adolescents, nulliparous or multiparous women. The reduction of the pain during insertion of the device could lead to increased use of the device. Purpose: This study aimed to assess the pain scores at the insertion of the 52 mg levonorgestrel-releasing intrauterine system (LNG-IUS) among nulligravidas, parous women with previous vaginal delivery and parous women with elective caesareandelivery without any previous labor or cervix dilatation. Patients and methods: The study included 413 women aged 15-49 years who opted for LNG-IUS placement for contraception or treatment of heavy menstrual bleeding. Pain at insertion was evaluated by using a Visual Analogue Scale (VAS). The women were divided as: (1) nulligravidas, (2) parous women with a previous vaginal delivery, or (3) parous women with elective caesarean-delivery without any previous labor or cervix dilatation. Results: Nulligravidas women presented a higher mean pain score, when compared to women with elective caesarean-delivery and women with previous vaginal delivery (6.6 ±2.0 vs 5.5 ±2.1 and 3.9 ±2.4, respectively; p<.001). Nulligravidas and women with elective caesarean-delivery were more likely to have pain classified as moderate or severe (in relation to absent or mild) than women with previous vaginal delivery (p<.001). Conclusions: Women with previous vaginal delivery had lower pain scores at LNG-IUS insertion when compared to nulligravidas and women with elective caesarean-delivery without any previous labor